Consumer‐resource interactions along urbanization gradients drive natural selection. (12th July 2018) - Start, Denon; Bonner, Colin; Weis, Arthur E; Gilbert, Benjamin
Abstract: Urbanization is an important component of global change. Urbanization affects species interactions, but the evolutionary implications are rarely studied. We investigate the evolutionary consequences of a common pattern: the loss of high trophic‐level species in urban areas. Using a gall‐forming fly, Eurosta solidaginis, and its natural enemies that select for opposite gall sizes, we test for patterns of enemy loss, selection, and local adaptation along five urbanization gradients. Eurosta declined in urban areas, as did predation by birds, which preferentially consume gallmakers that induce large galls. These declines were linked to changes in habitat availability, namely reduced forest cover in urban areas. Conversely, a parasitoid that attacks gallmakers that induce small galls was unaffected by urbanization. Changes in patterns of attack by birds and parasitoids resulted in stronger directional selection, but loss of stabilizing selection in urban areas, a pattern which we suggest may be general. Despite divergent selective regimes, gall size did not very systematically with urbanization, suggesting but not conclusively demonstrating that environmental differences, gene flow, or drift, may have prevented the adaptive divergence of phenotypes. We argue that the evolutionary effects of urbanization will have predictable consequences for patterns of species interactions and natural selection.